2016
DOI: 10.1177/2048872616683526
|View full text |Cite
|
Sign up to set email alerts
|

Baseline serum bicarbonate levels independently predict short-term mortality in critically ill patients with ischaemic cardiogenic shock

Abstract: In a large cohort of consecutive cardiogenic shock patients hospitalised in the ICU, low serum bicarbonate levels at admission independently predicted mortality. Given the widespread availability of blood gas analysers in ICUs, we propose baseline serum bicarbonate levels as an additional biomarker for identification and stratification of cardiogenic shock patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
6
24
0
Order By: Relevance
“…Previous studies in the USA and Switzerland have reported that a low serum bicarbonate level is associated with a higher mortality in patients with chronic kidney disease or ischemic cardiogenic shock . We suggest that lower initial serum bicarbonate levels at ED help to identify patients at risk of IHCA.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies in the USA and Switzerland have reported that a low serum bicarbonate level is associated with a higher mortality in patients with chronic kidney disease or ischemic cardiogenic shock . We suggest that lower initial serum bicarbonate levels at ED help to identify patients at risk of IHCA.…”
Section: Discussionmentioning
confidence: 65%
“…Serum bicarbonate, especially when assessed early in the course of patients at risk of CS may provide information regarding prognosis. In a recent study by Wigger et al serum bicarbonate decreased prior to significant elevation of lactate. A low bicarbonate level was a better predictor of 30‐day mortality than the highest recorded lactate level.…”
Section: Domains Of Patient Characteristicsmentioning
confidence: 89%
“…One study linked reduced BE to occult tissue hypo-perfusion [ 32 ]. Two further studies in patients with trauma and cardiogenic shock revealed an associated with mortality, but without clear explanations on the underlying pathomechanisms [ 24 , 25 ]. However, it should be taken into account that decreased BE, as increased lactate, has potential confounders and may be related to multiple etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, base excess was shown a strong predictor for mortality in specific subsets of ICU patients such as e.g. major trauma and in patients with cardiogenic shock [ 24 , 25 ]. However, whether the BD typically seen after cardiac surgery is actually related to the elevated lactate levels is currently controversially discussed [ 10 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%